2009
DOI: 10.1007/s10562-009-0227-1
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidation of p-Toluic Acid to Terephthalic Acid over T(p-Cl)PPMnCl/Co(OAc)2 Under Moderate Conditions

Abstract: The aerobic oxidation of p-toluic acid to terephthalic acid over tetra(p-chlorophenylporphinato)manganese (T(p-Cl)PPMnCl)/cobalt acetate was reported for the first time. The co-catalysis of T(p-Cl)PPMnCl/Co(OAc) 2 was also studied. The studies indicated that the PTA oxidation was influenced by the catalyst composition, catalyst concentrations and reaction conditions. A preliminary mechanism of this co-catalyzed oxidation reaction was proposed based on experimental observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…According to the literatures [48,49] and the observations in our reactions, taking the epoxidation of phenylethylene with H 2 O 2 as an example, a possible mechanism is proposed (Scheme 2). In the reaction, the catalyst Co(OAc) 2 provides a source of Co(II) (1), which reacts with the oxidant H 2 O 2 to form Co(III) = O (2).…”
Section: Resultsmentioning
confidence: 80%
“…According to the literatures [48,49] and the observations in our reactions, taking the epoxidation of phenylethylene with H 2 O 2 as an example, a possible mechanism is proposed (Scheme 2). In the reaction, the catalyst Co(OAc) 2 provides a source of Co(II) (1), which reacts with the oxidant H 2 O 2 to form Co(III) = O (2).…”
Section: Resultsmentioning
confidence: 80%
“…Radical oxidation plays important roles during the preparation of Terephthalic acid (Ogata et al, 1957;Jiang et al, 2008;Wang et al, 2013). Zuo et al (2010) found that the inert pure nitrogen atmosphere can be replaced by CO 2 , which can enhance the radical oxidation and can lead to a high yield of toluene and p-toluic acid (over 90%) in the liquid-phase oxidation system (Xiao et al, 2010). Some studies have further applied supercritical CO 2 for higher purity and a more active DCX/DCN process (P erez et al, 2011).…”
Section: Classic Radical Reactionsmentioning
confidence: 99%
“…5,10,15,20-Tetraphenylporphyrin (TPP; molecular mass, 614.74; CAS registry no., 917-23-7; chemical structure drawn in Figure ) and 5,10,15,20-tetraphenylporphyrin manganese­(III) chloride (TPPMnCl; molecular mass, 703.11; CAS registry no., 32195-55-4; chemical structure shown in Figure ), have been widely studied for several decades because of their high importance in many fields involving molecular electronics and sensors, , energy transfer, functional organic materials, , field-effect transistors, medicine, , and other applications in analytical chemistry . In addition, TPPMnCl has attracted great attention as an oxidation catalyst. This kind of metalloporphyrin has a catalytic effect on the activity of dioxygen under mild conditions, similar to cytochrome P-450 monooxygenase in biological phenomena. Based on that, the metalloporphyrin presents high catalytic activities and high selectivities in the catalytic oxidation of hydrocarbons without coreducing reagents; , consequently, the compound has received increasing attention from all areas of science.…”
Section: Introductionmentioning
confidence: 99%